Fitness and Wellness Lifestyles of the Personnel of Sultan Kudarat State University, Mindanao, Philippines - Vivencio L Calixtro Jr (Universitas Pendidikan Indonesia, 2021)
Healthy lifestyle is imperative to every human. Thus, it is needed for them to move lively and healthily. It makes one to be totally fit and well in order to fight common diseases. It refreshes the mind to avoid feeling of depression and exhaustion. This study examined the fitness and wellness lifestyles and health condition of Sultan Kudarat State University (SKSU) Personnel. It employed descriptive correlational research design which includes survey questionnaire in collecting data from 100 personnel. The results revealed that walking or brisk walking was rated highest holding it at least "2 to 3 times a week" or interpreted as "fit" in fitness lifestyles while the wellness lifestyles of the personnel revealed that manicure obtained the highest, holding it at least "7 to 10 times a year" or interpreted as "satisfied". On the other hand, pulmonary disease obtained the highest holding it at least "less evident" a year or interpreted as "healthy". It implies that they are not very much healthy due to some factors such as not engaging in physical activities. However, there was no significant relationship between the health condition of fitness and wellness lifestyles since participating in different physical, mental, and social activities is very imperative in order to achieve the total fitness and to become holistically productive personnel. The study concluded that the Personnel continually upheld their healthy lifestyles. They actively sustained total fitness in life. These were replicated on the whole lenience to work and to demonstrate everyday tasks professionally without any health-related condition.